The Influence of the Office Practice Program on Increasing Student Competence - Haedar Akib; Muh. Resky Febriyanto Zul Fadli Mustafa; Muh Darwis (ASHA Publishing, 2024)
This study aims to determine the description of the office practice program, the description of office practice, and the influence of the office practice program on improving the competence of Office Administration Education students at Universitas Negeri Makassar. This study is classified as an associative study with a quantitative approach. The sample in this study was 70 students of the Office Administration Education study program, Department of Administrative Sciences, Faculty of Social Sciences and Law, Universitas Negeri Makassar with a simple random sampling technique. In this study, the data collection techniques used were questionnaires and documentation. While the data analysis technique in this study used descriptive and inferential statistical analysis. The results of the study explain that the office practice variable is in the very good category, while the competence improvement variable is in the very good category. Based on the results of the product moment correlation test, the two variables have a strong relationship. Based on the simple linear regression analysis, it was concluded that there was a positive and significant influence of the office practice program on improving the competence of Office Administration Education students at Universitas Negeri Makassar. This study reveals that the implementation of the office practice program is running well so that competent students are realized and can compete in the industrial world and gain knowledge and experience that are useful for their future.